DIMINUTION OF HEAVY METALS IN INDUSTRIAL SOLID WASTE BY AN AMALGAMATION OF MYCO AND VERMI REMEDIATION - S, Gowthami; M, Thirumarimurugan; V. M, Sivakumar (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Due to the development of Industrialization and urbanization, a wide variety of industrial and consumer products, by products and solid waste has been produced. The solid waste generated constitutes the hazardous substance which possesses certain impacts on humans and their environment. In that heavy metal pollution from industries are the serious environmental problems. Rapid development in industries in the last few decades resulted in the strenuous task for finding to manage the waste generated. These hazardous solid wastes have been formulated into reusable end product by the process of bioremediation. Bioremediation is a natural process, which involves the use of organism to remove or neutralize the toxic pollutant from the contamination site. This review focus on the toxic effects of heavy metals on the environment and on the human health as well as the possible bioremediation method of these metals using fungus and earthworm. In order to conserve the environment and resources, the biological remediation by both fungus and earthworm for heavy metals and their efficiency have been summarised in detail.